Platelet-activating factor mediates trinitrobenzene induced dysmotility in the left colon - W. E. Longo; J. Standeven; B. Chandel; Y. Deshpande; A. M. Vernava; D. Kaminski (Mediators of Inflammation)
We investigated whether TNB alters colonic tissue levels of PAF at the expense of changes in colonic motility in the isolated perfused rabbit left colon. Colonic inflammation was induced by the intracolonic administration of 0.25 ml of 50% ethanol containing 30 mg of trinitrobenzene. Strain gauge transducers were sewn onto the serosal surface of the colon to evaluate colonic motility. TNB administration increased tissue levels of PAF and increased the average force of each colonic contraction. Pretreatment with the PAF receptor antagonist WEB-2170 prior to TNB infusion decreased tissue concentrations of PAF and ameliorated the altered motility parameters seen with TNB alone. These results suggest that PAF is stimulated by TNB and may participate in colonic dysmotility during inflammatory states.